Analisis Spasial Perubahan Tutupan Lahan Hutan Pasca Pembangunan Pusat Pemerintahan di Kabupaten Tana Tidung, Provinsi Kalimantan Utara - Viona Virinica; Belinda Ulfa Aulia (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Tana Tidung Regency accommodates its regional development by establishing a new government center and pursuing urban expansion from Tideng Pale urban area to Sesayap Hilir urban area. This article highlights a production forest area converted for the construction of a government center covering 404.42 hectares, along with multi-temporal forest land cover changes in 2015, 2020 and 2025. This transition zone is particularly vulnerable to uncontrolled spatial utilization due to increasing land demand and shifting spatial function boundaries. Spatial analysis of Land Cover Change using supervised classification and land cover overlay with the spatial plan and forest zone maps reveals that the majority of land changes occurred following the establishment of the government center between 2015, 2020 and 2025 with a vegetation cover decrease of 638.36 hectares and an increase in agricultural land of 477.7 hectares — indicating forest zone conversion to cultivation areas inconsistent with the spatial plan. This article recommends the need for compact regional development and strengthened spatial plan compliance through spatial use monitoring and participatory forest area management policies.